FAKTOR KEMENANGAN PARTAI BARISAN NASIONAL MALAYSIA DALAM PEMILU SELAMA 60 TAHUN (1957-2018) - Masitoh, Dewi (Universitas Medan Area, 2020)
This research aims to analyze the National Front Party?s (Barisan Nasional) strategies in carrying out their function as a political party in Malaysia. The problem focused on this paper is the victory factors of the Malaysian National Front Party in the Election for 60 years. To approach this problem, the theoretical framework will be used in this paper from Prof. Miriam Budiardjo?s concept, that the concept of a political party. The concept of political party is a tools and instruments for the people to participate and contribute in managing a country. Data from this paper has collected through secondary data and literature review and analyzed qualitatively. This research concluded that there were several factors that led to the National Front always winning in the election for 60 years, they are: First, the polarization and fragmentation politics in Malaysia, it?s called by Bumiputera policy, income gap and the Chinese Tsunami. Second, the influence of the New Economic Policy (NEP) as an affirmative action effort and there is a mix and match policy. Third, Gerrymandering and delineation in the form of an electoral system that is designed, so that the National Front always wins. Fourth, the instability and weakness of the Pakatan Rakyat as coalition opposition party.